Zika virus modulates human fibroblasts to enhance transmission success in a controlled lab-setting - Raimondas Mozūraitis; Karsten Cirksena; Mohammad Raftari; Melika Hajkazemian; Musa Mustapha Abiodun; Juela Brahimi; Sandra Radžiutė; Violeta Apšegaitė; Rasa Bernotienė; Lech Ignatowicz; Tessy Hick; Andreas Kirschning; et al. (Communications Biology)
Abstract Transmission of Zika virus (ZIKV) has been reported in 92 countries and the geographical spread of invasive virus-borne vectors has increased in recent years. Arboviruses naturally survive between vertebrate hosts and arthropod vectors. Transmission success requires the mosquito to feed on viraemic hosts. There is little specific understanding of factors that may promote ZIKV transmission-success. Here we show that mosquito host-seeking behaviour is impacted by viral infection of the vertebrae host and may be essential for the effective transmission of arboviruses like ZIKV. Human skin fibroblasts produce a variety of metabolites, and we show that ZIKV immediately alters gene/protein expression patterns in infected-dermal fibroblasts, altering their metabolism to increase the release of mosquito-attractive volatile organic compounds (VOCs), which improves its transmission success. We demonstrate that at the invasion stage, ZIKV differentially altered the emission of VOCs by significantly increasing or decreasing their amounts, while at the transmission stage of the virus, all VOCs are significantly increased. The findings are complemented by an extensive meta-proteome analysis. Overall, we demonstrate a multifaceted role of virus-host interaction and shed light on how arboviruses may influence the behaviour of their vectors as an evolved means of improving transmission-success.